Aspartate in tumor microenvironment and beyond: Metabolic interactions and therapeutic perspectives - Soon, Julian Wong; Manca, Maria Antonietta; Laskowska, Agnieszka; Starkova, Julia; Rohlenova, Katerina; Rohlena, Jakub (Biochimica et biophysica acta. Molecular basis of disease, 2024)
Aspartate is a proteinogenic non-essential amino acid with several essential functions in proliferating cells. It is mostly produced in a cell autonomous manner from oxalacetate via glutamate oxalacetate transaminases 1 or 2 (GOT1 or GOT2), but in some cases it can also be salvaged from the microenvironment via transporters such as SLC1A3 or by macropinocytosis. In this review we provide an overview of biosynthetic pathways that produce aspartate endogenously during proliferation. We discuss conditions that favor aspartate uptake as well as possible sources of exogenous aspartate in the microenvironment of tumors and bone marrow, where most available data have been generated. We highlight metabolic fates of aspartate, its various functions, and possible approaches to target aspartate metabolism for cancer therapy.
Keywords: Neoplasms; nádory; Animals; nádorové mikroprostředí; proliferace buněk; Tumor Microenvironment; lidé; Cell Proliferation; zvířata; kyselina asparagová; Aspartic Acid; Humans